Incidence of the game as a didactic resource in the teaching and learning processes of Natural Sciences - Altamirano Facino, A. B. (Facultad de Bioquímica y Ciencias Biológicas (UNL), 2021)
This research has investigated the application of recreational activities in the classroom that promote meaningful learning in students. This research is qualitative-quantitative and ethnographic in nature. It is oriented towards a socio-anthropological approach and, in effect, aims to enter a specific territory that, if applicable, is the classroom. Likewise, it is a descriptive-explanatory research. It consisted of conducting student surveys and an interview with the teacher. Said data collection instruments denoted that the application of didactic games in the classroom works as a reliable element to promote the meaningful learning of students in the Natural Sciences class.